Economic Evaluation of Yield-Increasing Wheat Seeds Using a Distance Function Approach. (20th March 2018) - Wree, Philipp; Sauer, Johannes; Wimmer, Stefan
Abstract : New wheat-breeding techniques, such as hybridization and genetic modification, show increasing yield potential. This study involves estimating multi-output multi-input production technology by stochastic frontier techniques to evaluate the economic value of this yield potential. An input-oriented distance function is formulated and applied to European Farm Accountancy Data of 23 European countries. Based on the analysis, an average shadow value is derived for the increase in the marginal yield of wheat that corresponded to 18.87 €/ha. Further, technical change, technical efficiency, and returns to scale are measured for different European regions.